Glory Falls - Rosche, Janine (Rosche, Janine. Madison River romance, 2021)
"Screenwriter Cecilia "Blue" Walker lost her daughter to the Madison River and her husband to another woman, and she yearns for something to restore her faith and her once-vibrant career. Hope arrives in the form of childhood friend Thomas Beck, a modest firefighter with a legacy of rescues. Haunted by his past, Thomas agrees to a movie adaptation of his story only because Blue, his longtime crush, will be the screenwriter. As Blue and Thomas work together to bring his heroism to the big screen, Hollywood threatens to shed light on secrets that could tear them apart."--Publisher.